The Death of Prophet Isa in Tafsīr al-Manār by Muḥammad ‘Abduh and Rashid Rida - Junaidi, Akhmad Arif (Jurnal Theologia, 2023)
This study discusses the story of the death of Prophet Isa in Tafsīr al-Manār by Muḥammad ‘Abduh and Muḥammad Rashid Rida. Most commentators interpret QS. Ali ‘Imrān: 55 and QS. al-Nisā’: 157-158 by stating that Isa is still alive today. Allah saved Isa from assassination and crucifixion attempts by his enemies by lifting him up to the sky. One day Prophet Isa will come back down to earth before the end of the world to kill the Dajjal who committed destruction and apostasy on earth. This study is a literature review because it relies entirely on literature data from tafsir books, books, and journals, both print and online. Descriptive analysis was used in this study by including a hermeneutic approach that looked at the triadic relationship between text, interpretation, and context of interpretation. This research found that in the Tafsīr al-Manār it was mentioned that the Prophet Isa had died a natural death. Prophet Isa was indeed saved by Allah but not by lifting him to heaven. Ordinary methods protected him, finally died naturally, and was placed in a glorious place in the sight of Allah. Muḥammad ‘Abduh and Rashid Rida argue that there is not a single Qur’anic verse that states that Isa is still alive. Thus, the sentences in the Qur’an state that Isa has died. The hadith that explains the appointment of Prophet Isa is also the ḥadīth āḥād that cannot be used as a postulate for matters concerning faith or i’tiqād. This finding has implications for the understanding that the Prophet will not return to earth before the world’s end.